EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN BAHASA LISAN ANAK USIA DINI - Ling Ling Halim; Marmawi R; Fadillah Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study was to determine the relationship between audio-visual media and oral language skills in children aged 5-6 years at Immanuel Christian Kindergarten Pontianak. The research method used is descriptive quantitative. The sample of this research data is children aged 5- 6 years in Immanuel Christian Kindergarten as many as 106 samples taken using simple random sampling method. The data taken were in the form of an assessment sheet for the child's oral language skills by the teacher and a questionnaire filled out by the parents of the students with the help of a google form. Data analysis used the product moment correlation formula and the results showed the rcount value of 0.633 > rtable of 0.195 at the significance level (α) = 0.05, so the conclusion of this study is that Hα is accepted and H0 is rejected, so there is a strong positive influence between the use of audio-visual media. with oral language skills of children aged 5-6 years in Immanuel Christian Kindergarten Pontianak.Keywords : Audio Visual, Learning Media, Oral Language, Skills.